Surface-dependent Conformations of Human Fibrinogen Observed by Atomic Force Microscopy under Aqueous Conditions - Sit, P. Sidney; Marchant, Roger E. (Thrombosis and Haemostasis, 1999)
Conformational differences in human fibrinogen under aqueous conditions on hydrophobic, positively charged and negatively charged surfaces, were examined by atomic force microscopy (AFM). Hydrophobic and positively charged surfaces were prepared by depositing octadecyltrichlorosilane (OTS) and 3-aminopropyltriethoxysilane (APTES) respectively on cleaned glass coverslips forming self-assembled monolayers. The negatively charged surface was prepared by freshly cleaving muscovite mica. AFM operated in fluid tapping mode with an ultrasharp carbon spike probe was used to obtain the molecular scale images. Fibrinogen displayed a characteristic trinodular structure on all three surfaces, although additional U-shaped conformations were observed on mica. In its native hydrated state, fibrinogen is well represented by three connected ellipsoids in close proximity. Quantitative dimensional analysis, which yielded structural information in three dimensions, indicates that surface-dependent structural deformation or spreading of fibrinogen increases according to the order: mica < APTES < OTS. Molecular length, and D and E domain widths of fibrinogen are increased, while the corresponding heights are decreased. The results provide direct evidence that material surface properties affect the conformational state of interacting fibrinogen.
Keywords: Surface-induced thrombosis; self-assembled monolayer; atomic force microscopy; protein conformations; mathematical morphology